Deuteration distribution estimation with improved sequence coverage for HX/MS experiments - Lou, Xinghua; Kirchner, Marc; Renard, Bernhard Y.; Köthe, Ullrich; Boppel, Sebastian; Graf, Christian; Lee, Chung-Tien; Steen, Judith A. J.; Steen, Hanno; Mayer, Matthias P.; Hamprecht, Fred (Bioinformatics, 2010)
Time-resolved hydrogen exchange (HX) followed by mass spectrometry (MS) is a key technology for studying protein structure, dynamics and interactions. HX experiments deliver a time-dependent distribution of deuteration levels of peptide sequences of the protein of interest. The robust and complete estimation of this distribution for as many peptide fragments as possible is instrumental to understanding dynamic protein-level HX behavior. Currently, this data interpretation step still is a bottleneck in the overall HX/MS workflow.
Gesehen am 18.04.2023